1974
DOI: 10.1097/00006842-197403000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Life Events and Diabetes in Adults

Abstract: Fluctuations in diabetic condition and changes in life events were studied in a group of 37 adult diabetic patients over a period of 8 to 18 months. Evidence is presented suggestive of a relationship between life events, particularly "undesirable" ones, and changes in diabetic condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

1982
1982
2003
2003

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…Some decades later a "diabetic personality", at increased risk of developing Type 1 diabetes, was suggested [33,34]. During the last decades, research has focussed on the occurrence of stressful B. H~iggl6f et al: Psychological stress as a risk factor for Type I diabetes life events prior to the clinical onset of Type 1 diabetes [23][24][25][35][36][37][38][39][40][41]. Results of these life event studies, however, are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Some decades later a "diabetic personality", at increased risk of developing Type 1 diabetes, was suggested [33,34]. During the last decades, research has focussed on the occurrence of stressful B. H~iggl6f et al: Psychological stress as a risk factor for Type I diabetes life events prior to the clinical onset of Type 1 diabetes [23][24][25][35][36][37][38][39][40][41]. Results of these life event studies, however, are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…These research reports have suggested that such dimensions as emotional tone in the family (1), mental health of the patient (2), and knowledge of diabetes management information (3), may be associated with level of metabolic control. Particular attention has been paid to the possible importance of psychologic stress as a factor associated with metabolic control (4)(5)(6)(7)(8)(9)(10)(11)(12). Laboratory investigations have suggested that psychologic stress may influence counterregulatory hormones (5,6), blood glucose levels (7,8), and free fatty acid and ketone body levels (7)(8)(9).…”
mentioning
confidence: 99%
“…Laboratory investigations have suggested that psychologic stress may influence counterregulatory hormones (5,6), blood glucose levels (7,8), and free fatty acid and ketone body levels (7)(8)(9). Other studies have suggested modest associations between patient reports of stressful life events and measures of glycemic control (10)(11)(12).…”
mentioning
confidence: 99%
“…A relationship between psychological factors and the metabolic control of diabetes has been extremely difficult to demonstrate by means of experimental research [ 14], Proper functioning of the family has also been observed to be connected with good metabolic control [15], In our own study, a large part of the patients in the psycho therapy group also had family support in their treatment efforts. It has been suggested that changes in stress and life situation may lead to a weakening of diabetes metabolic control [16,17], However, there are few wellconstructed studies dealing with this sub ject.…”
Section: Discussionmentioning
confidence: 99%